The Blood Compatibilities of Blood Purification Membranes and Other Materials Developed in Japan - Takaya Abe; Karen Kato; Tomoaki Fujioka; Tadao Akizawa (International Journal of Biomaterials)
The biocompatibilities in blood purification therapy are defined as “a concept to stipulate safety of blood purification therapy by an index based on interaction in the body arising from blood purification therapy itself.” The biocompatibilities are associated with not only materials to be used but also many factors such as sterilization method and eluted substance. It is often evaluated based on impacts on cellular pathways and on humoral pathways. Since the biocompatibilities of blood purification therapy in particular hemodialysis are not just a prognostic factor for dialysis patients but a contributory factor for long-term complications, it should be considered with adequate attention. It is important that blood purification therapy should be performed by consistently evaluating not only risks associated with these biocompatibilities but also the other advantages obtained from treatments. In this paper, the biocompatibilities of membrane and adsorption material based on Japanese original which are used for blood purification therapy are described.